Spatial Dimension of Czech Enterprise Support Policy: Where are Public Expenditures Allocated? - Jiří Novosák; Oldřich Hájek; Jana Novosáková; Jiří Koleňák (Review of Economic Perspectives, 2018)
The purpose of the present paper is to find whether the spatial distribution of enterprise support policy funds meet the spatial objectives stated in Czech strategic documents related to enterprise support policy. Are more funds allocated in lagging regions, and does enterprise support policy contribute more to the convergence objective, or are more funds allocated in core regions, and does enterprise support policy contribute more to the competitiveness objective? These questions are answered by evaluating the Structural (and Cohesion) Fund (SF) expenditures that were allocated on operations categorised as part of enterprise support policy (2007-2013). The dependent variable relates to 206 regions, and SF expenditures are calculated for every inhabitant of a region. Moreover, two types of SF operation are distinguished: (a) innovationoriented operations; and (b) other enterprise support operations. Three explanatory variables are defined using Principal Components Analysis (PCA), and these components are understood as: (1) the social disadvantage of regions; (2) the innovation environment of regions; and (3) the quality of regional entrepreneurial environments. The associations between the dependent and explanatory variables are subsequently evaluated by methods of correlation and regression analysis. The findings provide some evidence for both the convergence and competitiveness objectives. Nevertheless, this evidence is rather limited due to a low spatial concentration of SF allocation, and the compensatory effect between the two thematic types of SF operations. Hence, while the quality of their innovation environment has a positive influence on regional SF allocation regardless of the thematic focus of SF operations, socially disadvantaged regions received more funds for SF operations which are not innovation-oriented. The capacity of potential beneficiaries to prepare and submit many project proposals for SF co-financing is the main reason for high or low SF allocation.
Keywords: 330; enterprise support policy; cohesion policy; the Czech Republic; regional disparities